Entrepreneurship Trends and Challenges - Manuel Brito, Sílvio (IntechOpen, 2018)
Entrepreneurship is a powerful attitude that, in such a way, in the last few years, has become a discipline increasingly transversal to different areas of knowledge. Many times, we think about the things we want such as a good house, a brand new car, a beautiful relationship, a good friendship, and a good way to be in the world. Is that possible that you convert into an entrepreneur? This book shows some examples of that possibility, from simple people to a big organization. In all cases, if you become an entrepreneur, it will be for your taste and pleasure, a means to survive and enjoy the uncertainty, and rejoice that you have all these in your hands and will. Can you find out the trends and overcome the challenges? We would say yes. It all depends on whether you want to develop and apply this attitude.